Hack your organizational innovation: Literature review and integrative model for running hackathons - Ben Heller; Atar Amir; Roy Waxman; Yossi Maaravi (Journal of Innovation and Entrepreneurship, 2023)
This article aims to offer a comprehensive overview of the existing literature on the hackathon phenomenon to offer scholars a common ground for future research and managers and practitioners research-based guidelines on best planning and running a hackathon. A review of the most relevant literature on hackathons was conducted to serve as the research basis for our integrative model and guidelines. This article synthesizes the research on hackathons to offer comprehensible guidelines for practitioners while also providing questions for future hackathon researchers. We differentiate between the different design characteristics of hackathons while noting their advantages and disadvantages, discuss tools and methodologies for successful hackathon setup and execution step-by-step, and provide recommendations to encourage project continuity.
Keywords: 650; Creativity; Hackathon; Ideation; Innovation; Organizational Innovation